Clinical Profile of Pediatric Patients with Steroid-resistant Nephrotic Syndrome Treated by Cyclophosphamide, Cyclosporin A, Mycophenolate Mofetile and Tacrolimus in Hasan Sadikin General Hospital - Ahmedz Widiasta; Muhammad Khalid Jambak; Nanan Sekarwana (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2024)
Background: Steroid-resistant nephrotic syndrome is a major cause of chronic kidney disease in children and adolescents. These diseases require appropriate management, while in some developing countries; the availability of agents recommended by international guidelines is very limited. Research objectives: To determine and describe the patient profiles of pediatric Steroid Resistant Nephrotic Syndrome (SRNS) that use Cyclophosphamide (CPA), Cyclosporine(CyA), Tacrolimus, and Mycofenolat Mofetil (MMF) in Dr. Hasan Sadikin Hospital (RSHS), Bandung as a tertiary hospital in West Java, Indonesia. Methods and materials: This research used a retrospective study with crosssectional study design, total sampling method and medical record of pediatric (1-18 years old) patients from January 1st 2017–September 31st 2019 who were diagnosed as SRNS. Results : From 99 subjects that belonged to inclusion criteria, 35.4% pediatric SRNS patients were in the age group 6-10 years and 60.6% were males. Laboratorium profiles showed among all population, ureum <100 mg/dL were found as high as 97%, creatinine 0.3-1.0 mg/dL (71.7%) albumin >2,5 gr/dL (51.5%), negative hematuria (68.7%) , protein dipstick < 3 (50.5%), and LFG > 90 mL/min/1.73 m2 (79.8%).. The patients generally had use CPA (87.9%) and remission <6 month (51.5%). Conclusion: Profiles of pediatric patients are important to diagnose and prognose SRNS. By using these approaches, it is feasible to access and detect the most effective treatment for SRNS.